Quantitative Evaluation of Mean Vascular Density using CD34 as Immunohistochemical Marker in Variants of Ameloblastoma - Maryam, Hafiza Shahzadi (International Journal of Pathology, 2023)
Introduction: CD34 (Q-BEND 10) is a pan endothelial marker, monomeric glycoprotein and the cell surface trans membrane which is found in blood vessels of normal and neoplastic endothelial cells and use as a vascular marker for quantitative evaluation of angiogenesis. We determined the mean vascular density using CD34 as immunohistochemical marker in variants of Ameloblastoma.Material and Method: This is a descriptive cross-sectional study of 6 months duration from June 2018-dec 2018. Sample was collected using consecutive sampling technique (non-probability sampling) and 30 Formalin fixed paraffin embedded (FFPE) blocks of Ameloblastoma were collected. The mean vascular density (MVD) in ameloblastoma was evaluated using method described by Nielsen and McNagny. Three areas with the highest amount of vascularization (known as the hot spot) were selected under low magnification (×10) and micro vessels were counted in each specimen at ×40 magnification. The mean in three selected regions was considered as the MVD.Results: The study consisted of already diagnosed 30 cases of ameloblastoma. The age range was between 20 - 40 years followed by 50 to 60 years with mean age 36.13 + 16.0. CD34 shows positive expression for all 30 cases. Among them 14 (46.7%) were males and 16 (53.3%) were females. The most common site of tumor was mandible in 83.3% cases followed by maxilla in 16.7%. The most common type was follicular ameloblastoma comprising of 16 (53.3%) cases, followed by plexiform 8 (26.7%), unicystic 5 (16.7%) while only 1 (3.3%) was of mixed type. The MVD range from 9.33 - 26.3. MVD of all cases was found to be 19.12 + 7.8. Conclusion: It was concluded from this study that, CD34 can be used as a reliable endothelial marker to access MVD in different types of ameloblastoma.